2010
DOI: 10.1007/s11104-010-0283-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of soil water content in the rhizosphere

Abstract: Water flow from soil to plants depends on the properties of the soil next to roots, the rhizosphere. Although several studies showed that the rhizosphere has different properties than the bulk soil, effects of the rhizosphere on root water uptake are commonly neglected. To investigate the rhizosphere's properties we used neutron radiography to image water content distributions in soil samples planted with lupins during drying and subsequent rewetting. During drying, the water content in the rhizosphere was 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
336
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 330 publications
(356 citation statements)
references
References 39 publications
15
336
1
4
Order By: Relevance
“…In most coarsely textured soils of their investigation, plant available water increased with organic matter content, while in finer textured soils, an increase in water content at field capacity was only found at very high organic matter levels. On a smaller scale, Carminati et al (2010Carminati et al ( , 2011 recently demonstrated a distinct organic carbon effect in the rhizosphere via mucilage increasing water availability around roots. Plant water availability, however, is not only a function of soil storage capacity but also of soil profile depth.…”
Section: Soil Subsystemmentioning
confidence: 99%
“…In most coarsely textured soils of their investigation, plant available water increased with organic matter content, while in finer textured soils, an increase in water content at field capacity was only found at very high organic matter levels. On a smaller scale, Carminati et al (2010Carminati et al ( , 2011 recently demonstrated a distinct organic carbon effect in the rhizosphere via mucilage increasing water availability around roots. Plant water availability, however, is not only a function of soil storage capacity but also of soil profile depth.…”
Section: Soil Subsystemmentioning
confidence: 99%
“…A major advantage of NR as well as magnetic resonance imaging is the possibility to monitor water distribution and roots simultaneously (Menon et al, 2007;Oswald et al, 2008;Moradi et al, 2009;Carminati et al, 2010;Stingaciu et al, 2013). This is especially useful as water is a crucial factor ruling root allocation in soil (Hodge, 2010).…”
mentioning
confidence: 99%
“…More recently, experiments with time-resolved neutron radiography revealed unexpected water dynamics in the rhizosphere. Carminati et al (2010) found that the rhizosphere of lupines was wetter than the bulk soil during a drying period, but that following rewetting the rhizosphere remained markedly dry. This dry region extended to 1-2 mm from the root surface.…”
Section: Structural/water Imaging Using Neutron Radiography and Tomogmentioning
confidence: 99%
“…While root system architecture has in the past been derived from a range of computational models, it is now possible to measure it in situ (i.e., in the soil) using imaging techniques such as magnetic resonance imaging (MRI), X-ray computed tomography (X-ray CT) and neutron tomography, see Carminati et al (2010); Gregory et al (2003); Koebernick et al (2014);Metzner et al (2015); Mooney et al (2012); Moradi et al (2011);Oswald et al (2008) as a good starting point for the literature. These images can be utilised to build an image-based model for water and/or nutrient uptake by the root system.…”
Section: Modelling Rhizosphere Processes: State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation